Association between substance use and concurrent sexual relationships among urban slum dwellers in Nairobi, Kenya. Issue 11 (2nd November 2019) - Woldu, Dawit Okubatsion; Haile, Zelalem T.; Howard, Steve; Walther, Christine; Otieno, Aggrey; Lado, Bennet
ABSTRACT: While the overall incidence and prevalence of HIV/AIDS are declining in Africa, substance use-related HIV/AIDS is on the rise. The main objectives of this study were to elicit the types of commonly used substances and to examine the association between substance use and concurrent sexual relationships among slum dwellers in Kenya. Freelisting elicitation techniques were used to identify the most commonly used substances using 53 key informants. This was followed by a self-administered, structured questionnaire using a convenience sample of 506 participants. Findings from our freelisting analysis produced 27 substances that were used in the community. Analysis of the survey data shows that participants who reported using substances in the past three months were more likely to be involved in concurrent sexual relationships than those who did not (86.2% vs. 74.0%; p  = .002). In the multivariable model, the odds of ever having concurrent sexual relationships were higher among participants who used any substance in the past three months (aOR 2.46; 95% CI 1.37–4.42, p  < .01). The observed association between substance use and concurrent sexual relationships may be influenced by social and economic factors such as poverty and lack of opportunity among urban slum dwellers.